The leucosiid crabs described by Thomas Bell in 1855: original description and dates of publication (Crustacea: Decapoda: Brachyura) - Lee, B. Y.; Low, Martyn E.y. (Zootaxa, 2013)
Thomas Bell proposed 37 species- and 5 genus-group names for the Leucosiidae in four publications that appeared in 1855. The version appearing in the Proceedings of the Linnean Society of London is the earliest of these publications and the first available description of these taxa.